Pengaruh Layanan E-Payment dan E-Commerce terhadap Kinerja Supply Chain dalam Digitalisasi Usaha Mikro, Kecil, dan Usaha Menengah (UMKM) di Kabupaten Karawang - Nuraeni, Findi; Yanti; Rachpriliani, Awaliawati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Digitizing micro, small and medium enterprises (MSMEs) is very important, considering the many benefits associated with it. Indonesia, through government directives, has begun to develop digitization through the introduction of e-payment services and e-commerce services into the MSME supply chain, but there are still many challenges to face. In this study, we measure the effect of the use of e-payment and e-commerce services on the performance of the MSME supply chain to accelerate MSME digitalization. This study aims to obtain empirical evidence about the effect of perceived benefits, perceived ease of use and perceived risks on MSMEs to use e-payment services and e-commerce services as This study uses a theory, namely the Technology Acceptance Model (TAM), which is modified by adding risk perception variables. We collected data from 100 SMEs in Karawang Regency, then distributed it in the form of a questionnaire and the data analysis technique used was SmartPLS. The results show that there is a positive and significant influence between the variables of e-payment services and e-commerce services on the performance of the MSME supply chain in Karawang Regency. Keywords: Digitalization of MSMEs, e-payment services, e-commerce services, supply chain performance of micro, small and medium enterprises (MSMEs)